Optimalisasi Supervisi Kepemimpinan dalam Meningkatkan Profesionalitas Guru Madrasah Aliyah di Bengkulu - Okta Riski Tata Negara; Sofya Agustina; Helen Mahlena; Leza Apriyanti; Nadsrotul Furoidah; Adam Kurniawan (Al-Khair Journal: Management Education, 2024)
Abstract: Leadership supervision has not been optimally carried out, so the professionalism of teachers has not increased. The purpose of this study is to describe and analyze the optimization of leadership supervision in improving the professionalism of Madrasah Aliyah teachers in Bengkulu. Using a descriptive qualitative method. The results of the study show that: (1) Leadership Supervision has been carried out through supervision based on the Pancasila philosophy in improving the learning process, but there is still leadership of school principals who have not optimally supervised it; (2) The professionalism of some teachers has not improved, because some teachers have not been able to show their professionalism in their work; (3) Supervision has not been optimally carried out by the leadership, so the professionalism of teachers has not increased. Therefore, it can be concluded that the optimization of leadership supervision can improve the professionalism of teachers. Thus, it can be suggested, to improve the professionalism of teachers, then optimize leadership supervision in Madrasas.Keywords: Optimization, Leadership Supervision, and Teacher Professionalism Abstrak: Supervisi kepemimpinan belum optimal dilakukan, sehingga profesionalitas guru belum meningkat. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis optimalisasi supervisi kepemimpinan dalam meningkatkan profesionalitas guru Madrasah Aliyah di Bengkulu. Menggunakan metode kualitatif deskriptif. Hasil penelitian menunjukan bahwa: (1) Supervisi Kepemimpinan sudah dilaksanakan melalui pengawasan yang berlandasan falsafah pancasila dalam meningkatkan proses pembelajaran, namun masih ada kepemimpinan kepala sekolah yang belum optimal melakukan supervisi; (2) Profesionalitas sebagian guru belum meningkat, karena sebagian guru belum mampu menunjukkan keprofesionalannya dalam bekerja; (3) Supervisi belum optimal dilakukan oleh kepemimpinan, sehingga profesionalitas guru belum meningkat. Oleh karena itu, dapat disimpulkan bahwa optimalisasi supervisi kepemimpinan dapat meningkatkan profesionalitas guru. Dengan demikian dapat disarankan, untuk meningkatkan profesionalitas guru, maka optimilisasikanlah surpevisi kepemimpinan di Madrasah.Kata kunci: Optimalisasi, Supervisi Kepemimpinan, dan Profesionalitas Guru